KAJIAN ETNOBOTANI TUMBUHAN OBAT DI DESA MENGKIANG KECAMATAN SANGGAU KAPUAS KABUPATEN SANGGAU - Haryono, Dipta; Wardenaar, Evy; Yusro, Fathul (Universitas Tanjungpura, 2014)
The purpose of this study is to determine the Malay community knowledge in Mengkiang village Sanggau Regency in the use of medicinal plants and to know content of secondary metabolites in plants through the stages of phytochemical test. The research was conducted by interview, observation, literature study and test phytochemicals of the plant that have not been identified through the literature. The results showed there are 60 types of medicinal plant into a distribution of 37 family, with is the highest family is Euphorbiaceae (5 species), the highest habitus is a herb (25 species/41.67%), used parts of plant are leaves (35 species/58.33%) , highest processing by boiling (35 species/58.33%), the highest used by drink (39 species/65%), 55 species/91.67%) is included in the form of a single herb. The result of phytochemical known that the Pisang hias plant (Heliconia colinsiana) contain alkaloids, saponins, quinones, flavonoids; jomai leaves and lomak leaves contain alkaloids, tannins, leaves hair kuncur (Tibouchina heteromalla) contain alkaloids, saponins, tannins and susu kambing leaves (Euphorbia hirta L) contains alkaloids, tannins and flavonoids. Keywords : Ethnobotany, medicinal plants, Malay ethnic, village Mengkiang